Female genital mutilation/cutting in sudan and subsequent pelvic floor dysfunction - Özer Birge; Aliye Nigar Serin; Mehmet Sait Bakır (BMC, 2021)
Abstract Background We aimed to evaluate the socio-demographic characteristics of women with female genital mutilation/cutting (FGM/C) and the results of FGM/C due to pelvic floor dysfunction. Results The prevalence of FGM/C was 87.2% in Sudan and Type 3 (50.4%) was the most prevalent, followed by Type 2 (35%) and Type 1 (8.5%). In the multinominal logistic regression analysis performed to show the effect of FGM/C on pelvic organ prolapse (POP), it was observed that FGM/C frequency in POP group 2 was statistically similar when POP group 1 was taken as reference category. In the evaluation for symptomatic POP (POP group 3), risk of developing POP in patients without FGM/C was significantly lower than patients with type 3 FGM/C with a rate of 82.9% (OR(odds ratio): 0.171 (p: 0.002), (Confidence Interval (CI) %95; 0.058-0.511). Risk of developing POP rate in patients with type 1 FGM/C was 75% (OR:0.250 (p: 0.005), CI %95; 0.094-0.666) and in patients with type 2 FGM/C was 78.4% (OR:0.216 (p: 0.0001), CI%95; 0.115-0.406). In the multinominal logistic regression analysis including other variables affecting POP, when group 1 was taken as the reference category, it was found that the possibility of developing mild POP (group 2) decreased in FGM/C type 1 and 2 compared to FGM/C type 3 but it was not statistically significant. However, the evaluation for the symptomatic POP group showed up a significantly lower risk of developing POP in patients with type 2 FGM/C compared to patients with type 3 FGM/C, with a rate of 58.4%. (OR:0.419 (p: 0.016), CI%95; 0.206-0.851) (Table 3). In addition, older age was found to be significant risk factor for increasing symptomatic POP (p: 0.003). Conclusions Type 2 and 3 FGM/C continues to be an important health problem in terms of complications that may develop in advanced ages as well as many short-term complications as a result of mechanical or physiological deterioration of the female genital anatomy.